Wire Guided Wide Local Excision of Clinically Undetectable Breast Cancer - Initial Experience in Bangladesh (Journal of Surgical Sciences, 2020)
Background: With the rise of awareness of breast cancer and better screening mammography, there are increasing number of breast cancers detected before becoming clinically evident. These cancers are mostly treated by wide local excision under guidance of a wire which is put with mammogram and/or USG. In Bangladesh this procedure has never been done. We started it in Surgical Oncology Division in BSMMU with the collaboration of Department of Radiology.Methods: We have performed the procedure on 7 patients within 19 months. All of them had USG and mammography detected small lesions. The average size being 7.24mm. From needle biopsy 3 cases showed suspicious cytology, 4 had IDCC, and 1 had DCIS. Wire was put in all cases under USG guidance. Wire Guided Wide Local Excision was performed in all cases. $ patients underwent SLNB.Results: The age range was between 26 to 55 years with the average age of 43.86 years. 4 of them being post-menopausal. One case came benign. Other were malignant with clear margins. One case had close margin, which was later re-excised. All cases were sent for adjuvant therapy. Histopathology showed 4 patients of invasive ductal carcinoma, 1 patient each of invasive lobular carcinoma, DCIS and 1 being benign.Conclusion: This well-established procedure can be performed in Bangladesh to meet the goal of ensuring adequate treatment and cosmesis of the patients with impalpable cancer, amidst constrained facilities.Journal of Surgical Sciences (2019) Vol. 23(2): 81-86